Non-destructive testing techniques for inspection of heat exchanger tubes - Ren, Yong. (2008)
This dissertation covers the basic principles and methodologies of some nondestructive testing techniques (NDTs) on heat exchanger tubes used in the petrochemical industry. This project focuses on analysis and comparison of five NDT techniques. They are conventional eddy current testing (ECT), remote field eddy current testing (RFT), magnetic flux leakage testing (MFL), ultrasonic internal rotary inspection system (IRIS) and optical technique - videoprobe. Three materials of aluminum brass, copper nickel alloys and carbon steel were used. The aluminum brass samples with real corrosion, pits and cracks were used for comparison to determine the effectiveness of ECT, IRIS and videoprobe techniques. One copper nickel tube and three carbon steel tubes with artificial flaws were tested. The copper nickel tube was tested by ECT, IRIS and videoprobe while the carbon steel tubes were inspected by RFT, MFLT and IRIS techniques. The emphasis was put on comparison of different techniques regarding the flaw detectability. The author has concluded through experiments that the eddy current test may give higher percentage of tube wall loss (thickness thining) than actual defect depth if it is on the internal surface. The baffle support signal in remote field eddy current testing will shadow the defect signals if the defects are small and under the support baffle. The amplitude of the defect signal in magnetic flux leakage testing is related not only to its depth but also its area. The minimum detectable thickness of the internal rotary inspection system is limited to its resolution.